Let be nonzero perfect squares such that . The equation has the following properties:
Among all such , pick the one such that the discriminant is minimum. Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since a , b , c are all perfect square numbers, we can rewrite them as squared numbers for some positive integers s , t , u below:
a = s 2 ; c = t 2 ; b = u 2
Now from b = a + c , u 2 = s 2 + t 2 .
That means the integers s , t , u form a Pythagorean triple, and when we evaluate the quadratic discriminant, it will result in absolute difference between two squares:
b 2 − 4 a c = ( a + c ) 2 − 4 a c = a 2 − 2 a c + c 2 = ( a − c ) 2 = ∣ a − c ∣
Substituting a = s 2 ; c = t 2 , we will get:
∣ a − c ∣ = ∣ s 2 − t 2 ∣ = ∣ s − t ∣ ∣ s + t ∣
Since the condition restricts that the discriminant is prime, that means ∣ s − t ∣ = 1. Otherwise, the product will be a composite number.
Then in case s = t + 1; u 2 = ( t + 1 ) 2 + t 2 = 2 t 2 + 2 t + 1.
Clearly, u is odd and equals to 2 n + 1 for some integer n .
( 2 n + 1 ) 2 = 2 t 2 + 2 t + 1
4 n 2 + 4 n = 2 t 2 + 2 t
2 n 2 + 2 n = t 2 + t
2 n [ n + 1 ] = t [ t + 1 ]
This product is a multiplication of 2 consecutive natural numbers, which is also a multiplication of 2 consecutive numbers when it's divided by 2. Of all the consecutive pairs, only 3 × 4 = 2 [ 2 × 3 ] fits the constraint. (For t = s + 1, it will have similar results.)
In other words, (3 , 4 , 5) and (4 , 3 , 5) are the only applicable triples for (s , t , u). Hence, the discriminant will equal to 2 5 2 − 4 ( 9 × 1 6 ) = 7 .
Nonetheless, if a = 4 2 ; c = 3 2 , the roots will equal to 3 2 ( 2 5 + 7 ) = 3 2 3 2 = 1 or 3 2 ( 2 5 − 7 ) = 3 2 1 8 , which never exceeds 1. Therefore, a = 3 2 ; c = 4 2 .
Hence, d = 1 8 ( 2 5 + 7 ) = 1 8 3 2 = 9 1 6 = a c .
Therefore, a b c d = 9 × 2 5 × 1 6 × ( 9 1 6 ) = 1 6 × 5 = 8 0 .